Effects of 21 days of altitude on sea-level anaerobic performance in competitive swimmers - Martino, M.; Myers, K.; Bishop, P. (Medicine & Science in Sports & Exercise, 1995)
The effects of anaerobic training at 2800 m on sea-level (SL) measures of: 100 m sprint, lactate recovery slope, upper-body Wingate peak power and mean power, and fatigue index were evaluated. An experimental group (E: 12F, 8M) and an unmatched control group (C: 7F, 6M) were compared. Both groups trained under the same protocol. It was found that sprint swimming speed (-5.56 s E and -3.13 s C) and peak power (34.5 E and 6.62 C) were the only two measures that changed significantly between the two groups. Non-significant changes occurred in all other variables. It was concluded that altitude training significantly enhanced anaerobic improvements at SL, particularly in the performance of the sprint swimming task. That conclusion should be viewed with skepticism since the experimental and control groups were not matched. The possibility of confounding factors causing group differences cannot be discounted. As with many previous altitude studies, unless rigorous control over all possible influential variables is exercised, meaningful and unequivocal results will not be forthcoming.